Aggregation-induced luminescence magnetically encoded microspheres based on active swelling and preparation method and application thereof

Through the active swelling method, AIE molecules are embedded and magnetic particles are deposited on the surface of the luminescent magnetically encoded microspheres in the aggregation-induced luminescent magnetically encoded microspheres, which solves the problem of poor fluorescence stability in the aggregation state, and achieves high coding capacity and stability Aggregation induces luminescent magnetically encoded microspheres.

CN118165727BActive Publication Date: 2025-02-25AIE INSTITUTE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410136758.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2025-02-25
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

In the prior art, traditional organic materials are prone to fluorescence quenching in aggregation state, which limits the encoding capacity and stability, and the encoding capability of quantum dot-encoded microspheres is limited by the reabsorption between fluorescent signals and the color-split effect. , it is difficult to achieve high coding capacity and stability.

Method used

AIE molecules are embedded in the blank polymer microspheres by active swelling method, and magnetic particles are generated on the surface of the microspheres by in-situ precipitation of iron salts, and the dosage and mass ratio of AIE molecules and iron salts are regulated to prepare uniform particle sizes. And the aggregation with strong fluorescence uniformity induced luminescent magnetically encoded microspheres.

Benefits of technology

High encoding capacity is achieved, single-wavelength AIE encoding capacity reaches 9 levels, and detection stability is improved, avoiding the problem of easy quenching of traditional fluorescent materials under magnetic substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118165727B_ABST
    Figure CN118165727B_ABST
Patent Text Reader

Abstract

The present invention discloses an aggregation-induced luminescence magnetically encoded microsphere based on active swelling and a preparation method and application thereof; the aggregation-induced luminescence magnetically encoded microsphere comprises an AIE polymer microsphere and a magnetic particle; the AIE polymer microsphere is obtained by embedding an AIE molecule in a blank polymer microsphere by an active swelling method, and the amount of the AIE molecule in the active swelling method is 0.01-10wt% of the amount of the blank polymer microsphere; the magnetic particle is deposited on the surface of the AIE polymer microsphere by an in-situ precipitation method of an iron salt, and the amount of the iron salt in the in-situ precipitation method is 0.1-25wt% of the amount of the blank polymer microsphere; and the ratio of the mass amount of the AIE molecule to the mass amount of the iron salt is 0.0004-2. The CV value of the flow fluorescence signal of the magnetically encoded microsphere of the present invention and the CV value of the flow FCS are both less than 10%, and the encoding peak is ≥9 weight; an important fluorescent material is added to the encoding element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of in vitro diagnosis, and in particular relates to an aggregation-induced luminescence magnetic encoding microsphere based on active swelling, and a preparation method and application thereof. Background Art

[0002] The development and completion of the human genome and proteome in recent years has led to a huge demand for large-scale analysis of biomolecules, which has promoted the rapid development of liquid suspension biochips with encoded microspheres as the core. Liquid suspension biochips with rapid high-throughput flow cytometry and magnetic separation as analytical methods have gradually become a new goal for accurate diagnosis by performing rapid and high-throughput multiplex detection of markers such as proteins, nucleic acids and small molecules. Among them, the development of encoded microspheres with high encoding capacity and stability is still a huge challenge. The design of suitable encoded microspheres has the following requirements: high photostability, good anti-magnetism, large number of codes, no reabsorption and crosstalk effects, etc.

[0003] Spectral signals are widely used in the construction of liquid biochips due to their flexible encoding and fast decoding speed. At present, the commonly used spectral encoding materials are mainly organic materials, quantum dots, upconversion dots and photonic crystals, etc. Quantum dots have become popular encoding materials due to their high brightness and narrow emission spectrum, but the encoding ability of quantum dots is limited by the reabsorption and cross-color effect between quantum dot fluorescence signals, which limits the application of quantum dot encoding microspheres.

[0004] At present, commercial liquid biochip Luminex system and BD's cytometric bead array all use organic dyes for encoding, but traditional organic materials have fluorescence quenching in the aggregated state, which limits the encoding capacity and stability of traditional organic materials. The new aggregation-induced emission (AIE) material discovered by the team of Academician Tang Benzhong in 2001 is a promising encoding material for the preparation of encoded microspheres, because AIE materials can achieve in-situ enhancement of fluorescence signals during the aggregation process. Aggregation-induced emission materials have properties such as large Stokes shift, strong resistance to photobleaching, and anti-magnetism, and are an excellent encoding microsphere material. However, there are few public reports on the efficient preparation of magnetic fluorescence encoding using AIE materials. Therefore, it is very necessary to develop a technology for the efficient and direct generation of aggregation-induced emission magnetic encoded microspheres. Summary of the invention

[0005] In order to solve the shortcomings of the prior art, the present invention aims to provide an aggregation-induced luminescence magnetically encoded microsphere based on active swelling and a preparation method and application thereof. The aggregation-induced luminescence magnetically encoded microsphere has uniform particle size and high encoding capacity, and can achieve 9 or more encodings.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] An aggregation-induced luminescence magnetically encoded microsphere based on active swelling, comprising an AIE polymer microsphere and magnetic particles;

[0008] The AIE polymer microspheres are obtained by embedding AIE molecules inside blank polymer microspheres through an active swelling method, wherein the amount of AIE molecules used in the active swelling method is 0.01-10wt% of the amount of blank polymer microspheres;

[0009] The magnetic particles are deposited on the surface of the AIE polymer microspheres by an in-situ precipitation method of iron salts, wherein the amount of iron salts used in the in-situ precipitation method is 0.1-25wt% of the amount of blank polymer microspheres;

[0010] The ratio of the mass amount of the AIE molecule to the mass amount of the iron salt is 0.0004-2.

[0011] Preferably, the blank polymer microspheres are selected from at least one of polystyrene microspheres, polymethyl methacrylate microspheres and polyglycidyl acrylate microspheres;

[0012] Further preferably, the blank polymer microspheres are selected from polystyrene microspheres or polyglycidyl acrylate microspheres.

[0013] Preferably, the magnetic particles are Fe3O4;

[0014] Preferably, the iron salt is selected from at least one of a ferric salt and a divalent iron salt; the ferric salt is selected from at least one of ferric chloride hexahydrate and anhydrous ferric chloride; the divalent iron salt is selected from at least one of ferrous chloride tetrahydrate, ferrous chloride dihydrate, ferrous sulfate and ferrous sulfate heptahydrate;

[0015] Further preferably, considering the uniformity of magnetic particles deposited on the surface of the AIE polymer microspheres, the iron salt is a compound of a trivalent iron salt and a divalent iron salt, wherein the mass amount of the trivalent iron salt is 10% to 60% of the mass amount of the divalent iron salt.

[0016] Preferably, the AIE molecule is selected from at least one of the following AIE-1 molecules to AIE-16 molecules:

[0017]

[0018]

[0019] Alkyl chain in AIE-1 molecule - C8H 17 Each is independently a branched alkyl group or a straight-chain alkyl group. The alkyl chain in the AIE-11 molecule is -C6H 13 Each is independently a branched chain alkyl or a straight chain alkyl.

[0020] Preferably, the active swelling method is to allow the AIE molecules to swell with the blank polymer microspheres via a swelling agent so that the AIE molecules are embedded inside the blank polymer microspheres;

[0021] Further preferably, in the active swelling method, the swelling agent is selected from at least one of dichloromethane, tetrahydrofuran, chloroform, anisole, benzyl alcohol and toluene, and the particle size of the blank polymer microspheres ranges from 0.03 μm to 50 μm;

[0022] More preferably, the particle size of the blank polymer microspheres ranges from 0.5 μm to 10 μm.

[0023] Preferably, the in-situ precipitation method is to add an alkaline solution to react with the iron salt chelated on the surface of the AIE polymer microspheres in situ to generate magnetic particles that are deposited on the surface of the AIE polymer microspheres.

[0024] Further preferably, in the in-situ precipitation method, the surface of the AIE polymer microspheres is modified by sulfonation, and the alkaline solution is selected from at least one of sodium hydroxide solution, ammonia water, potassium hydroxide solution and sodium bicarbonate solution.

[0025] Preferably, the CV value of the flow fluorescence signal and the CV value of the flow FCS of the active swelling-based aggregation-induced luminescence magnetic encoded microspheres are both less than 10%, and the encoding peak is ≥ 9-fold.

[0026] The above-mentioned method for preparing active swelling-based aggregation-induced luminescence magnetically encoded microspheres comprises the following steps:

[0027] S1. Preparation of AIE polymer microspheres by active swelling method

[0028] (1) dispersing blank polymer microspheres in water to obtain a microsphere dispersion;

[0029] (2) dissolving the AIE molecules in a swelling agent to obtain an AIE swelling agent solution;

[0030] (3) adding the AIE swelling agent solution described in step (2) to the microsphere dispersion described in step (1), and after ultrasonic treatment, closing the reactor to carry out swelling reaction. After the reaction is completed, volatilizing and removing the swelling agent to obtain AIE polymer microspheres;

[0031] S2. Preparation of Aggregation-Induced Luminescence Magnetic Encoded Microspheres Based on Active Swelling by In-situ Precipitation

[0032] The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is increased for reaction, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation-modified surfaces. The microspheres are mixed with iron salt and water for reaction, and the supernatant is removed by centrifugation to obtain iron salt-chelated AIE polymer microspheres. An alkaline solution is added, the temperature is increased, and the iron salt reacts in situ to generate magnetic particles that are deposited on the surface of the AIE polymer microspheres. The supernatant is removed by centrifugation to prepare aggregation-induced luminescence magnetically encoded microspheres based on active swelling.

[0033] Preferably, the preparation method of the active swelling-based aggregation-induced luminescence magnetically encoded microspheres comprises the following steps:

[0034] S1. Preparation of AIE polymer microspheres by active swelling method

[0035] (1) dispersing blank polymer microspheres in water to obtain a microsphere dispersion;

[0036] (2) dissolving the AIE molecules in a swelling agent to obtain an AIE swelling agent solution;

[0037] (3) adding the AIE swelling agent solution described in step (2) to the microsphere dispersion described in step (1), and after ultrasonic treatment at an ultrasonic power of 50 W to 400 W for 1 min to 30 min, a closed reactor is used for swelling reaction for 0.5 h to 4 h. After the reaction is completed, the swelling agent is volatilized to obtain AIE polymer microspheres;

[0038] S2. Preparation of Aggregation-Induced Luminescence Magnetic Encoded Microspheres Based on Active Swelling by In-situ Precipitation

[0039] The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is raised to 30°C to 100°C and the reaction is carried out for 4h to 12h, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation modified on the surface. The microspheres are mixed with iron salt and water, and the mixture is immersed in the solution for reaction for 0.5h to 10h, and the supernatant is removed by centrifugation to obtain iron salt chelated AIE polymer microspheres. An alkaline solution is added, and the temperature is raised to 60°C to 120°C and the reaction is carried out for 0.5h to 4h. The iron salt reacts in situ to generate magnetic particles which are deposited on the surface of the AIE polymer microspheres. The supernatant is removed by centrifugation to prepare aggregation-induced luminescence magnetically encoded microspheres based on active swelling.

[0040] Further preferably, in step S1, the ultrasonic power of step (3) is 300W, the ultrasonic treatment time is 5 minutes, and the time for volatilizing and removing the swelling agent is 2 hours to 10 hours. More preferably, the time for volatilizing and removing the swelling agent is 4 hours.

[0041] Further preferably, in step S2, the soaking reaction time is 2 h to 4 h.

[0042] Preferably, in step S1, the mass amount of blank polymer microspheres in the microsphere dispersion is 0.1% to 20% of the mass amount of water;

[0043] Further preferably, the mass amount of blank polymer microspheres in the microsphere dispersion is 0.5% to 10% of the mass amount of water.

[0044] Preferably, in step S1, the mass amount of the AIE molecules in the AIE swelling agent solution is 0.0005% to 50% of the mass amount of the swelling agent;

[0045] Preferably, in step S2, the mass concentration of the sulfuric acid solution is 70% to 99%; the mass amount of the AIE polymer microspheres is 1% to 30% of the mass amount of the sulfuric acid solution;

[0046] Further preferably, the mass concentration of the sulfuric acid solution is 98.3%; and the mass amount of the AIE polymer microspheres is 5% to 20% of the mass amount of the sulfuric acid solution.

[0047] Preferably, in step S2, the mass dosage of the iron salt is 0.0005% to 25% of the mass dosage of water; the mass dosage of the alkaline solution is 0.1% to 50% of the mass dosage of water; the mass concentration of the alkaline solution is 1% to 10%;

[0048] Preferably, the water in step S1 and step S2 is ultrapure water; the centrifugal speed is 3000 rpm to 6000 rpm, the centrifugal time is 5 min to 60 min, and the number of centrifugation is more than three times.

[0049] The above-mentioned active swelling-based aggregation-induced luminescence magnetically encoded microspheres are used in in vitro non-disease diagnostic testing.

[0050] The AIE magnetically encoded microspheres prepared based on active swelling and in-situ generation technology provided by the present invention have the characteristics of good antimagnetism, large Stokes shift, high fluorescence intensity and good photostability.

[0051] The present invention proposes a new technology for efficiently preparing aggregation-induced emission (AIE) magnetically encoded microspheres by combining active swelling and in-situ generation. AIE molecules are actively swelled into the interior of the microsphere matrix through hydrophobic interaction and concentration difference, and magnetic particles are generated on the surface of the microspheres by an in-situ generation method of iron salts. At the same time, by regulating the dosage and mass ratio of AIE molecules and iron salts, single-wavelength aggregation-induced emission magnetically encoded microspheres with uniform particle size and strong fluorescence uniformity and high encoding capacity are obtained. The microspheres have excellent detection stability and can achieve 9-fold or more encoding.

[0052] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:

[0053] (1) Compared with the fluorescent materials of traditional magnetic encoded microspheres, the AIE materials of the active swelling aggregation-induced luminescence magnetic encoded microspheres of the present invention improve the encoding capacity of the magnetic encoded microspheres and solve the problem that traditional fluorescent materials are easily quenched under magnetic matrices. In high magnetic content microspheres, the single-wavelength AIE encoding capacity reaches 9-fold capacity.

[0054] (2) The present invention uses a simple swelling volatilization and in-situ generation technology to encapsulate hundreds of millions of AIE molecules inside the microspheres, and deposits magnetic particles in situ on the surface of the microspheres. By adjusting the amount and mass ratio of AIE molecules and iron salts, AIE magnetic fluorescent encoded microspheres with optimal performance are obtained.

[0055] (3) The active swelling-based aggregation-induced emission magnetically encoded microspheres of the present invention have typical aggregation-induced emission properties. AIE molecules are embedded in the interior of the microspheres and can emit strong fluorescence in the aggregates. At the same time, the strong light resistance of the AIE material itself provides excellent detection stability.

[0056] (4) The preparation method of the active swelling-based aggregation-induced luminescence magnetic encoded microspheres of the present invention is simple, which realizes the effective application of AIE molecules in the preparation of encoded microspheres, adds an important fluorescent material to the encoding element, and provides a new strategy for the core raw materials of protein biochips. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a scanning electron microscope image of the aggregation-induced luminescence magnetically encoded microspheres prepared in Example 1.

[0058] Figure 2 Schematic diagram of flow encoding of aggregation-induced luminescence magnetically encoded microspheres prepared in Example 1. DETAILED DESCRIPTION

[0059] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0060] The blank polymer microspheres in the examples and comparative examples are polystyrene polymer microspheres with a diameter of 5 μm, which are from AIE Research Institute and have a product number of NWKPB-500.

[0061] The encoding data of the aggregation-induced luminescence magnetically encoded microspheres were tested using an analytical flow cytometer. The CV value of the flow fluorescence signal represented the uniformity of the fluorescence swelling, and the CV value of the flow FCS represented the uniformity of the particle size of the microspheres. According to the detection performance requirements of in vitro diagnostics, the CV value of the flow fluorescence signal and the CV value of the flow FCS must be less than 10% to determine that the encoding was successful, otherwise it failed.

[0062] Example 1

[0063] Weigh 1 g of blank polymer microspheres and disperse them in 100 g of water to obtain a microsphere dispersion;

[0064] AIE-3 molecules were dissolved in 10 mL of tetrahydrofuran to obtain an AIE swelling agent solution; the two solutions were mixed together (the mass of AIE molecules accounted for 0.01 wt% of the mass of blank polymer microspheres), and ultrasonically treated at a power of 100 W for 1 min. After the closed swelling for 2 h, the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0065] Ferrous sulfate heptahydrate and ferric chloride hexahydrate were mixed with 100g water in a mass ratio of 2:1 (the total mass of iron salt accounted for 25wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surface were added. After soaking and reacting for 1h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain iron salt-chelated AIE polymer microspheres. 50mL of 1mol / L sodium hydroxide solution was added, the temperature was raised to 80℃, and the reaction was carried out for 2h. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. The microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0066] Embodiment 2-9

[0067] The preparation method and test of aggregation-induced luminescence magnetically encoded microspheres in Example 2-9 are different from those in Example 1 only in that the AIE molecular mass accounts for the mass of the blank polymer microspheres and the total mass of the iron salt accounts for the mass of the blank polymer microspheres (see Table 1); the rest are the same.

[0068] The morphology of the aggregation-induced luminescence magnetically encoded microspheres of Example 1 was observed using a field emission SEM electron microscope. The microspheres were regular spherical structures with a statistical particle size of about 5 μm (e.g. Figure 1 ).

[0069] The encoding data of the aggregation-induced luminescence magnetically encoded microspheres of Example 1 were tested using an analytical flow cytometer. The schematic diagram of the flow encoding of the aggregation-induced luminescence magnetically encoded microspheres is shown in FIG. Figure 2 .

[0070] The flow fluorescence signal CV value and flow FCS CV value of the aggregation-induced luminescence magnetic encoded microspheres of test examples 1-9 were tested using an analytical flow cytometer (see Table 1), and the encoding was successful.

[0071] Comparative Example 1

[0072] Weigh 1 g of blank polymer microspheres and disperse them in 100 g of water to obtain a microsphere dispersion;

[0073] 1g of AIE-3 molecules were dissolved in 10mL of tetrahydrofuran to obtain an AIE swelling agent solution, and the two solutions were mixed together (the mass of AIE molecules accounted for 100wt% of the mass of blank polymer microspheres), and ultrasonically treated at a power of 100W for 1min. After the closed swelling for 2h, the solvent was evaporated for 4h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50mL of concentrated sulfuric acid (98.3wt%), the temperature was raised to 80°C, and the reaction was carried out for 8h; the microspheres were centrifuged at a speed of 5000rpm, and then resuspended in water, and repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0074] A total mass of 50 mg of ferrous sulfate heptahydrate and ferric chloride hexahydrate were mixed with 100 g of water in a mass ratio of 2:1 (the total mass of iron salts accounted for 5 wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surfaces were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This was repeated three times to obtain iron salt-chelated AIE polymer microspheres; 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salts reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres; the microspheres were centrifuged at 5000 rpm and resuspended in water. This was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0075] The encoding data of the aggregation-induced emission magnetically encoded microspheres were tested using an analytical flow cytometer. Due to the excessive amount of AIE molecules used, the fluorescence leakage during the swelling process was serious. The CV value of the flow fluorescence signal was 22.6%, and the CV value of the flow FCS was 15.7%, indicating encoding failure (Table 1).

[0076] Comparative Example 2

[0077] Weigh 1 g of blank polymer microspheres and disperse them in 100 g of water to obtain a microsphere dispersion;

[0078] 0.001g AIE-3 molecules were dissolved in 10mL tetrahydrofuran to obtain an AIE swelling agent solution, and the two solutions were mixed together (the mass of AIE molecules accounted for 0.1wt% of the mass of blank polymer microspheres), and ultrasonically treated at a power of 100W for 1min, and after closed swelling for 2h, the solvent was evaporated open for 4h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50mL concentrated sulfuric acid (98.3wt%), the temperature was raised to 80°C, and the reaction was carried out for 8h; the microspheres were centrifuged at a speed of 5000rpm, and then resuspended in water, and repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0079] A total mass of 350 mg of ferrous sulfate heptahydrate and ferric chloride hexahydrate were mixed with 100 g of water in a mass ratio of 2:1 (the total mass of iron salts accounted for 35 wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surfaces were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain iron-chelated AIE polymer microspheres. 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salts reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. The microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0080] The encoding data of aggregation-induced luminescence magnetically encoded microspheres were tested using an analytical flow cytometer. Due to the excessive total amount of iron salt used, the microspheres were severely aggregated during the in situ generation process. The CV value of the tested flow fluorescence signal was 5.3%, and the CV value of the flow FCS was 20.5%, indicating encoding failure (Table 1).

[0081] Comparative Example 3

[0082] Weigh 1 g of blank polymer microspheres and disperse them in 100 g of water to obtain a microsphere dispersion;

[0083] 0.8g AIE-3 molecules were dissolved in 10mL tetrahydrofuran to obtain an AIE swelling agent solution, and the two solutions were mixed together (the mass of AIE molecules accounted for 80wt% of the mass of blank polymer microspheres), and ultrasonically treated at a power of 100W for 1min, and after closed swelling for 2h, the solvent was evaporated for 4h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50mL concentrated sulfuric acid (98.3wt%), the temperature was raised to 80℃, and the reaction was carried out for 8h; the microspheres were centrifuged at a speed of 5000rpm, and then resuspended in water, and repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0084] A total mass of 350 mg of ferrous sulfate heptahydrate and ferric chloride hexahydrate were mixed with 100 g of water in a mass ratio of 2:1 (the total mass of iron salts accounted for 35 wt% of the mass of blank polymer microspheres), and the above-obtained AIE polymer microspheres with sulfonated surfaces were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain iron-chelated AIE polymer microspheres. 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salts reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. The microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0085] The encoding data of aggregation-induced emission magnetically encoded microspheres were tested using an analytical flow cytometer. Due to the excessive use of AIE molecules and the total amount of iron salts, the fluorescence leakage during the swelling process was serious and the microspheres were severely agglomerated during the in situ generation process. The CV value of the flow fluorescence signal tested was 24.2%, and the CV value of the flow FCS was 13.6%, indicating encoding failure (Table 1).

[0086] The data of the aggregation-induced luminescence magnetically encoded microspheres with different AIE molecule dosages and total iron salt dosages in Examples 1-9 and Comparative Examples 1-3 are shown in Table 1. As can be seen from Table 1, only when the AIE molecule dosage / blank polymer microsphere mass, the total iron salt dosage / blank polymer microsphere mass and the AIE molecule mass / total iron salt mass of Examples 1-9 are within a certain range can the encoding be successful, while none of Comparative Examples 1-3 can be encoded successfully.

[0087] Table 1 Effects of different AIE molecule contents and total iron salt mass content on streaming encoding results

[0088]

[0089] Example 10

[0090] Weigh 0.5 g of blank polymer microspheres and disperse them in 50 g of water to obtain a microsphere dispersion;

[0091] 5 mg of AIE-5 molecules were dissolved in 5 mL of dichloromethane to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 1 min, closed and swollen for 2 h, and then the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 30 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0092] A total mass of 0.05 g of ferrous sulfate heptahydrate and ferric chloride hexahydrate was mixed with 50 g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification obtained above were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain iron salt chelated AIE polymer microspheres. 30 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. The microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0093] The encoding data of aggregation-induced luminescence magnetically encoded microspheres were tested using an analytical flow cytometer. The CV value of the flow fluorescence signal was 5.3%, and the CV value of the flow FCS was 2.5%, indicating successful encoding.

[0094] Embodiment 11

[0095] Weigh 1 g of blank polymer microspheres and disperse them in 75 g of water to obtain a microsphere dispersion;

[0096] 25 mg of AIE-5 molecules were dissolved in 7.5 mL of dichloromethane to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 5 min, closed and swollen for 2 h, and then the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 75 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0097] A total mass of 0.5 g of ferrous sulfate heptahydrate and ferric chloride hexahydrate was mixed with 100 g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification obtained above were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. The process was repeated three times to obtain iron salt chelated AIE polymer microspheres; 75 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres; the microspheres were centrifuged at 5000 rpm and resuspended in water. The process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0098] The encoding data of aggregation-induced luminescence magnetically encoded microspheres were tested using an analytical flow cytometer. The CV value of the flow fluorescence signal was 4.3%, and the CV value of the flow FCS was 3.5%, indicating successful encoding.

[0099] Example 12

[0100] Weigh 2.5 g of blank polymer microspheres and disperse them in 150 g of water to obtain a microsphere dispersion;

[0101] 50 mg of AIE-7 molecules were dissolved in 15 mL of tetrahydrofuran to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 5 min, closed and swollen for 2 h, and then the solvent was evaporated for 6 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0102] A total mass of 0.5 g of ferrous chloride heptahydrate and ferric chloride hexahydrate was mixed with 75 g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification obtained above were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. The process was repeated three times to obtain iron salt chelated AIE polymer microspheres; 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres; the microspheres were centrifuged at 5000 rpm and resuspended in water. The process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0103] The encoding data of aggregation-induced luminescence magnetically encoded microspheres were tested using an analytical flow cytometer. The CV value of the flow fluorescence signal was 5.3%, and the CV value of the flow FCS was 4.5%, indicating successful encoding.

[0104] Embodiment 13

[0105] Weigh 10 g of blank polymer microspheres and disperse them in 500 g of water to obtain a microsphere dispersion;

[0106] 150 mg of AIE-11 molecules (alkyl chain -C6H 13 The AIE polymer microspheres were prepared by mixing the two solutions together, ultrasonically treating them at a power of 100 W for 10 min, sealing and swelling for 2 h, evaporating the solvent for 10 h, and centrifuging to remove the supernatant to obtain the AIE polymer microspheres. The obtained AIE polymer microspheres were added to 100 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at a speed of 5000 rpm, and then resuspended in water, and the reaction was repeated three times to obtain the AIE polymer microspheres with sulfonated surface modification.

[0107] A total mass of 1g of ferrous chloride heptahydrate and ferric chloride hexahydrate was mixed with 50g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification obtained above were added. After soaking and reacting for 1h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain iron salt chelated AIE polymer microspheres; 100mL of 1mol / L sodium hydroxide solution was added, the temperature was raised to 80℃, and the reaction was carried out for 2h. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres; the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0108] The encoding data of aggregation-induced luminescence magnetically encoded microspheres were tested using an analytical flow cytometer. The CV value of the flow fluorescence signal was 6.2%, and the CV value of the flow FCS was 3.8%, indicating successful encoding.

[0109] Embodiment 14

[0110] Weigh 0.1 g of blank polymer microspheres and disperse them in 12.5 g of water to obtain a microsphere dispersion;

[0111] 1 mg of AIE-14 molecules were dissolved in 2 mL of chloroform to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 1 min, closed and swollen for 2 h, and then the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 15 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0112] A total mass of 0.02 g of ferrous sulfate heptahydrate and ferric chloride hexahydrate was mixed with 20 g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification obtained above were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain iron salt chelated AIE polymer microspheres. 15 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. The microspheres were centrifuged at 5000 rpm and resuspended in water. This process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0113] The encoding data of aggregation-induced luminescence magnetically encoded microspheres were tested using an analytical flow cytometer. The CV value of the flow fluorescence signal was 2.3%, and the CV value of the flow FCS was 5.5%, indicating successful encoding.

[0114] Embodiment 15

[0115] Weigh 1 g of blank polymer microspheres and disperse them in 125 g of water to obtain a microsphere dispersion;

[0116] 50 mg of AIE-15 molecules were dissolved in 5 mL of dichloromethane to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 1 min, closed and swollen for 2 h, and then the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0117] A total mass of 0.2 g of ferrous sulfate heptahydrate and ferric chloride hexahydrate was mixed with 100 g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification obtained above were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. The process was repeated three times to obtain iron salt chelated AIE polymer microspheres; 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres; the microspheres were centrifuged at 5000 rpm and resuspended in water. The process was repeated three times to obtain aggregation-induced luminescence magnetically encoded microspheres.

[0118] The encoding data of aggregation-induced luminescence magnetically encoded microspheres were tested using an analytical flow cytometer. The CV value of the flow fluorescence signal was 3.3%, and the CV value of the flow FCS was 2.5%, indicating that the encoding was successful.

[0119] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.

Claims

1. An aggregation-induced luminescence magnetically encoded microsphere based on active swelling, characterized in that: Including AIE polymer microspheres and magnetic particles; The AIE polymer microspheres are obtained by embedding AIE molecules inside blank polymer microspheres through an active swelling method, wherein the amount of AIE molecules used in the active swelling method is 0.01-10wt% of the amount of blank polymer microspheres; the blank polymer microspheres are selected from at least one of polystyrene microspheres, polymethyl methacrylate microspheres and polyglycidyl acrylate microspheres; The magnetic particles are deposited on the surface of the AIE polymer microspheres by an in-situ precipitation method of iron salts, wherein the amount of iron salts used in the in-situ precipitation method is 0.1-25wt% of the amount of blank polymer microspheres; the iron salts are a compound of trivalent iron salts and divalent iron salts, wherein the mass amount of the trivalent iron salts is 10% to 60% of the mass amount of the divalent iron salts; The ratio of the mass amount of the AIE molecule to the mass amount of the iron salt is 0.0004-2; The AIE molecule is selected from at least one of the following AIE-1 molecules to AIE-16 molecules:

2. The active swelling-based aggregation-induced luminescence magnetically encoded microspheres according to claim 1, characterized in that: The magnetic particles are Fe3O4; The trivalent iron salt is selected from at least one of ferric chloride hexahydrate and anhydrous ferric chloride; the divalent iron salt is selected from at least one of ferrous chloride tetrahydrate, ferrous chloride dihydrate, ferrous sulfate and ferrous sulfate heptahydrate.

3. The active swelling-based aggregation-induced luminescence magnetically encoded microspheres according to claim 1, characterized in that: The active swelling method is to allow the AIE molecules to swell with the blank polymer microspheres through a swelling agent so that the AIE molecules are embedded inside the blank polymer microspheres; The in-situ precipitation method is to add an alkaline solution to react with the iron salt chelated on the surface of the AIE polymer microsphere in situ to generate magnetic particles that are deposited on the surface of the AIE polymer microsphere.

4. The active swelling-based aggregation-induced luminescence magnetically encoded microspheres according to claim 3, characterized in that: In the active swelling method, the swelling agent is selected from at least one of dichloromethane, tetrahydrofuran, chloroform, anisole, benzyl alcohol and toluene, and the particle size of the blank polymer microspheres ranges from 0.03 μm to 50 μm; In the in-situ precipitation method, the surface of the AIE polymer microspheres is modified by sulfonation, and the alkaline solution is selected from at least one of sodium hydroxide solution, ammonia water, potassium hydroxide solution and sodium bicarbonate solution.

5. The method for preparing active swelling-based aggregation-induced luminescence magnetically encoded microspheres according to any one of claims 1 to 4, characterized in that: The steps include: S1. Preparation of AIE polymer microspheres by active swelling method (1) dispersing blank polymer microspheres in water to obtain a microsphere dispersion; (2) dissolving the AIE molecules in a swelling agent to obtain an AIE swelling agent solution; (3) adding the AIE swelling agent solution described in step (2) to the microsphere dispersion described in step (1), and after ultrasonic treatment, closing the reactor to carry out swelling reaction. After the reaction is completed, volatilizing and removing the swelling agent to obtain AIE polymer microspheres; S2. Preparation of Aggregation-Induced Luminescence Magnetic Encoded Microspheres Based on Active Swelling by In-situ Precipitation The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is increased for reaction, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation-modified surfaces. The microspheres are mixed with iron salt and water for reaction, and the supernatant is removed by centrifugation to obtain iron salt-chelated AIE polymer microspheres. An alkaline solution is added, the temperature is increased, and the iron salt reacts in situ to generate magnetic particles that are deposited on the surface of the AIE polymer microspheres. The supernatant is removed by centrifugation to prepare aggregation-induced luminescence magnetically encoded microspheres based on active swelling.

6. The method for preparing active swelling-based aggregation-induced luminescence magnetically encoded microspheres according to claim 5, characterized in that: The following steps are involved: S1. Preparation of AIE polymer microspheres by active swelling method (1) dispersing blank polymer microspheres in water to obtain a microsphere dispersion; (2) dissolving the AIE molecules in a swelling agent to obtain an AIE swelling agent solution; (3) adding the AIE swelling agent solution described in step (2) to the microsphere dispersion described in step (1), and after ultrasonic treatment at an ultrasonic power of 50 W to 400 W for 1 min to 30 min, a closed reactor is used for swelling reaction for 0.5 h to 4 h. After the reaction is completed, the swelling agent is volatilized to obtain AIE polymer microspheres; S2. Preparation of Aggregation-Induced Luminescence Magnetic Encoded Microspheres Based on Active Swelling by In-situ Precipitation The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is raised to 30°C to 100°C and the reaction is carried out for 4h to 12h, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation modified on the surface. The microspheres are mixed with iron salt and water, and the mixture is immersed in the solution for reaction for 0.5h to 10h, and the supernatant is removed by centrifugation to obtain iron salt chelated AIE polymer microspheres. An alkaline solution is added, and the temperature is raised to 60°C to 120°C and the reaction is carried out for 0.5h to 4h. The iron salt reacts in situ to generate magnetic particles which are deposited on the surface of the AIE polymer microspheres. The supernatant is removed by centrifugation to prepare aggregation-induced luminescence magnetically encoded microspheres based on active swelling.

7. The method for preparing active swelling-based aggregation-induced luminescence magnetically encoded microspheres according to claim 5, characterized in that: In step S1, the mass amount of blank polymer microspheres in the microsphere dispersion is 0.1% to 20% of the mass amount of water; In step S1, the mass amount of the AIE molecules in the AIE swelling agent solution is 0.0005% to 50% of the mass amount of the swelling agent; In step S2, the mass concentration of the sulfuric acid solution is 70% to 99%; the mass amount of the AIE polymer microspheres is 1% to 30% of the mass amount of the sulfuric acid solution; In step S2, the mass dosage of the iron salt is 0.0005% to 25% of the mass dosage of water; the mass dosage of the alkaline solution is 0.1% to 50% of the mass dosage of water; the mass concentration of the alkaline solution is 1% to 10%; The water in step S1 and step S2 is ultrapure water; the centrifugal speed is 3000 rpm to 6000 rpm, the centrifugal time is 5 min to 60 min, and the number of centrifugation is more than three times.

8. Use of the active swelling-based aggregation-induced luminescence magnetically encoded microspheres according to any one of claims 1 to 4 in in vitro non-disease diagnostic testing.

Citation Information

Patent Citations

  • Micron-sized aggregation-induced emission polymer microsphere as well as preparation method and application thereof

    CN113683717A

  • Preparation method of core-shell heterogeneous magnetic aggregation-induced emission fluorescent microspheres

    CN114634813A